Analisis Penggunaan Pasir Kuarsa dengan Tambahan Superplasticizer terhadap Kapasitas Kuat Tekan dan Tarik Belah Beton - Wahidah Sulkaeda Aseh Syahda; Mustakim, Mustakim; Misbahuddin, Misbahuddin (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
Aggregate is one of the concrete forming materials that has the largest composition in the concrete mixture, the large number of uses of concrete in construction results in an increase in the need for concrete materials, triggering rock mining as one of the materials forming concrete on a large scale. This study aims to determine the effect of quartz sand substitution and superplasticizer on the compressive and tensile strength of concrete, and to determine the results of the comparison of each mixture of pure sand substitution with quartz sand plus additive superplasticizers on the compressive strength and tensile strength of concrete. The method used in this study was an experiment at the Civil Engineering Structure and Material Laboratory, University of Muhammadiyah Parepare. From January to April 2023. The results showed that the results of compressive strength testing of concrete at the age of 28 days on normal concrete with an average of 27.45 Mpa. For a variation of 25% quartz sand with an average of 20.75 Mpa. For the CPC 300 variation with an average compressive strength of 25.10 Mpa. As for the BPK500 variation with an average compressive strength of 20.76 Mpa, while for the results of concrete tensile testing that pays attention to variations in superplasticizer mixtures with 4 variations, namely BN, BPK0, BPK300 and BPK500, the results of the tensile strength test test obtained an average value of 10.44 MPa. For the 25% variation, an average value of 4.22 MPa was obtained. For the BPK300 variation, an average value of 5.11 MPa was obtained. As for the CPC 500 variation with an average value of 5.22 MPa.